考虑抗弯刚度不确定性的简支梁桥损伤定位方法 = Damage localization method for simply supported bridge with flexural stiffness uncertainty considered - 王艺霖 Wang, Yi-lin (2015)
为了处理主梁抗弯刚度的不确定性,实现简支梁桥主梁的准确损伤定位!通过进行影响线分 析!基于位移影响线二次差值的概念提出了一个损伤定位指标----跨中位移影响线差值指标(DIILMSD), 通过测量移动荷载下主梁跨中的竖向位移增量即可基于DIILMSD指标建立相应的损伤定位方法。研究结果表明：对于局部抗弯刚度具有不确定性的实际主梁，其损伤位置可通过对比损伤前后的DIILMSD数据图形来进行有效的识别，如果某一点(x2=x'+m)和邻近!个点连线的斜 率发生了变化!则说明损伤出现在区间[x',x'+m]或[l- x'- m,l- x' (之内)损伤定位的效果可 通过改变荷载加载值的大小来进行调节。In order to deal with flexural stiffness uncertainty of main girder and then localize the damage of main girder for simply supported bridges accurately, a damage localization index based on the idea of second order difference of displacement influence line－difference index of influence line for mid-span displacement (DIILMSD), was presented by employing influence line analysis. Only the incremental vertical displacement of the mid-span under mobile load needed to be measured by using this index. Subsequently, the damage localization method based on DIILMSD was established. The results show that the damage positions of actual main girders with local flexural stiffness uncertainty can be effectively detected by comparing two DIILMSD graphs before and after damage. If the slopes of two attachment lines between one point (x2=x'+m) and its two adjacent points change, it can be known that damage occurs within the region [x',x'+m] or [l- x'- m,l- x']. In addition, the effect of damage localization can be adjusted by changing the value of load.